2020
DOI: 10.1111/acem.13889
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Biomarkers for the Diagnosis of Adult Community‐acquired Pneumonia: A Meta‐analysis

Abstract: Background Biomarkers such as C‐reactive protein (CRP) and procalcitonin may help distinguish community‐acquired pneumonia (CAP) from other causes of lower respiratory tract infection. Methods We performed a systematic review of the literature to identify prospective studies evaluating the accuracy of a biomarker in patients with acute cough or suspected CAP. We performed parallel abstraction of data regarding study inclusion, characteristics, quality, and test accuracy. Study quality was evaluated using QUADA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
0
19
2
4
Order By: Relevance
“…[23] However, some researchers found that the CRP level did not improve the prediction of pneumonia; instead, it can help clinicians make a decision regarding the use of antibiotics. [24,25] In contrast to previous studies [11,20], we found that a hsCRP level of 1.64 mg/L had a negative likelihood ratio of 0.07 in the ROC analysis, which means it was a strong predictor of the absence of pneumonia in patients with normal or low leukocyte counts. Further investigations showed that three patients had a hsCRP level less than 1.64 mg/L in the pneumonia group, two of whom were diagnosed with COVID-19 according to the Chinese management guidelines (version 7.0) [15].…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…[23] However, some researchers found that the CRP level did not improve the prediction of pneumonia; instead, it can help clinicians make a decision regarding the use of antibiotics. [24,25] In contrast to previous studies [11,20], we found that a hsCRP level of 1.64 mg/L had a negative likelihood ratio of 0.07 in the ROC analysis, which means it was a strong predictor of the absence of pneumonia in patients with normal or low leukocyte counts. Further investigations showed that three patients had a hsCRP level less than 1.64 mg/L in the pneumonia group, two of whom were diagnosed with COVID-19 according to the Chinese management guidelines (version 7.0) [15].…”
Section: Discussioncontrasting
confidence: 86%
“…It was identi ed as a predictor of pneumonia in several studies. [11,[20][21][22] A CRP level ≤ 10 mg/L was useful for ruling out CAP in most patients. [11]Steurer et al found there was no pneumonia diagnosed when the CRP levels were < 10 mg/L or if the CRP levels were between 11 and 50 mg/L and the patient did not complain of dyspnea and fever associated with cough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CRP testing has also been shown to decrease antibiotic prescription rates and is sometimes used as a decision aid to determine whether or not to request a CXR [105][106][107][108][109][110]. Further, CRP has been suggested as the preferred biomarker, alone and as part of a CDR for diagnosis of CAP in primary care [70,111,112].…”
Section: Crpmentioning
confidence: 99%